The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/lpor.201800258
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh‐Q Photonic Nanocavity Devices on a Dual Thickness SOI Substrate Operating at Both 1.31‐ and 1.55‐µm Telecommunication Wavelength Bands

Abstract: A feasible method for integrating several silicon (Si) photonic devices with operating wavelengths separated by several hundred nanometers on a single chip will greatly help increasing capacities of small optical communication modules. This work demonstrates the integration of two photonic crystal nanocavity devices that exhibit ultrahigh quality factors (Q) and operate at the 1.31‐ and 1.55‐µm bands. A dual thickness Si‐on‐insulator substrate forms the base of the device. The two nanocavity patterns are defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…By using ultra‐thin flakes, fine tuning can be done with high predictability and reproducibility because of the quantized shifts arising from the atomically precise thickness. This is in contrast to continuous mode shifts obtained in conventional methods such as chemical etching, [ 42 ] coating of photochromic films, [ 43 ] and condensation of gases. [ 44 ] In addition, the stackable and removable 2D materials offer a new degree of freedom for reconfigurable cavities.…”
Section: Resultsmentioning
confidence: 75%
“…By using ultra‐thin flakes, fine tuning can be done with high predictability and reproducibility because of the quantized shifts arising from the atomically precise thickness. This is in contrast to continuous mode shifts obtained in conventional methods such as chemical etching, [ 42 ] coating of photochromic films, [ 43 ] and condensation of gases. [ 44 ] In addition, the stackable and removable 2D materials offer a new degree of freedom for reconfigurable cavities.…”
Section: Resultsmentioning
confidence: 75%
“…By using ultra-thin flakes, fine tuning can be done with high predictability and reproducibility because of the quantized shifts arising from the atomically precise thickness. This is in contrast to continuous mode shifts obtained in conventional methods such as chemical etching [39], coating of photochromic films [40], and condensation of gases [41]. In addition, the stackable and removable 2D materials offer a new degree of freedom for reconfigurable cavities.…”
Section: Resultsmentioning
confidence: 85%
“…Compared with the earlier reported Si Raman lasers, [141] the PhC nanocavity enables the laser size with a much smaller scale for large-area integration in PIC. [145] In 2019, a follow-up work by Kuwabara et al [148] demonstrated two PhC nanocavity Si Raman lasers on the same chip with different layer thicknesses. The two lasers with different substrate thicknesses are fabricated with the same process.…”
Section: Raman Lasers On Siliconmentioning
confidence: 99%
“…[ 145 ] In 2019, a follow‐up work by Kuwabara et al. [ 148 ] demonstrated two PhC nanocavity Si Raman lasers on the same chip with different layer thicknesses. The two lasers with different substrate thicknesses are fabricated with the same process.…”
Section: Raman Lasers On Siliconmentioning
confidence: 99%